Studies to determine antidiarrhoeal and spasmolytic activities of extract of Aegle marmelos. L fruit (Bangladesh Journal of Medical Science, 2018)
Objective: To investigate and determine the antidiarrhoeal and spasmolytic potential of fruit of Aegle marmelos is due to CCBs compounds and not tannic acid.Materials and methods: The extract of ripe and dry fruit of A. marmelos (Am.Cr) was prepared in methanol: water (70:30). The antidiarrhoeal activities of the extract, loperamide and tannic acid were studied in vivo; in castor oil induced diarrhoeal model in mice whereas spasmolytic effect was studied in vitro; in isolated mice ileum. Calcium channel blocking (CCB) activity was investigated after preincubation of mice ileum by Am. Cr or loperamide and subsequent adding of K+80 mM.Results: Am. Cr inhibited castor oil-induced diarrhoea: onset of diarrhoea, total no. of faeces, and total no. of wet faeces dose-dependently, the dose of 800 mg/mL was found statistically significant, total weight of feces and total weight of wet faeces were also inhibited. Concentration-dependent inhibition of spontaneous contraction and contractile effect of K+80 mM after pre-incubation by Am. Cr were confirmed in isolated mice ileum. The results of Am. Cr are comparable with Loperamide. Tannic acid produced neither antidiarrhoeal effect nor exhibited CCB activity, however relaxant effect was observed in isolated mice ileum.Conclusion: The antidiarrhoeal and spasmolytic effects of Am.Cr may be mediated through compounds which posses CCB effect. Tannic acid exhibited relaxant effect only which is not sufficient evidence scientifically to classify as antidiarrhoeal.Bangladesh Journal of Medical Science Vol.17(2) 2018 p.205-211